Analisa karakteristik briket campuran bahan dasar tempurung kelapa, kulit kacang, dan kulit kedelai terhadap nilai kalor menggunakan metode torefaksi microwave - Kuntang Winangun; Muh. Malyadi; Achmat Rifay (TURBO [Tulisan Riset Berbasis Online], 2021)
Fossil fuel is a non-renewable fuel. It is necessary to find alternative energies by converting coconut shell waste, peanut shell waste, and soybean shell waste into briquettes. This study aims to utilize agricultural waste and determine the test parameters for the value of ash content, moisture content, temperature, flame duration, and calorific value of the briquette mixture of peanut shell, soybean shell, and coconut shell with variations in composition. This research was carried out by converting coconut shell, peanut shells, and soybean shells into charcoal with a carbonization process for 3 hours, the all waste charcoals were pulverized and sieved with a 60 mesh sieve, mixed with the addition of 10% tapioca flour adhesive, printed with a pressure of 250 psi. The briquettes were dried using a microwave machine with a power of 450 watts for 30 minutes. The results showed the highest value in briquette ingredient 1 with a mixture of 30% coconut shell, 50% peanut shell, and 20% soybean shell with a good moisture content value of 6.32%, an ash content value of 0.084%, a combustion heat value of 484.90C, the duration of the combustion flame was 1 hour 50 minutes 26 seconds, and the highest heating value was 7447.964 cal/g. The calorific value that does not meet the standard material 2 with a composition of 30% coconut shell, 20% peanut shell and 50% soybean shell produces a heat below the SNI, namely 4649.299 cal/g. For moisture and ash content in all materials meet the standards.Keywords: Briquettes, coconut shell, peanut shell, soybean shell.